Use of dynamic multilines for the management of sorghum anthracnose - Costa, Rodrigo Véras; Zambolim, Laércio; Silva, Dagma Dionísia; Cota, Luciano Viana; Casela, Carlos Roberto (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to evaluate the efficiency of dynamic multilines, using genetic mixing in populations of three‑way hybrids, in the management of sorghum anthracnose, caused by the fungus Colletotrichum sublineolum. Eighteen three‑way hybrids were obtained from seven different lines containing genes for resistance to the disease. The 25 genotypes of hybrids and lines were evaluated in field conditions. In some hybrids, a higher resistance level was observed when compared to that of the more resistant line used in the crosses, indicating an additive effect of the resistance genes of the different lineages in the composition of the final resistance of hybrids. The use of dynamic multilines reduced the disease intensity in field and increased productivity. This strategy makes it possible to use lineages that have desirable agronomic characteristics, but are susceptible to anthracnose.